Legal culture: characteristics and specifics (on the example of contemporary Kazakhstan) - G R Absattarov (RUDN journal of Sociology, 2014)
The article considers the legal culture as an ‘ideal phenomenon’ providing value meanings for the outlook of the Kazakhs and the basis for the development of the population legal consciousness. The author focuses on the national significance of the legal, civil society and the development of new legal social ideals, norms and rules, examines key problems and contradictions in the legal culture of today’s Kazakhstan.